2010
DOI: 10.1007/s11250-010-9754-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hematological and biochemical parameters in sheep naturally and persistently infected with a border disease virus

Abstract: In this study, we investigated the changes occurring in the activities of determining the biochemical and hematological parameters in persistently infected sheep with border disease virus (BDV) and control sheep. While cholesterol, aspartate aminotransferase, lactate dehydrogenase, high-density lipoprotein, and glucose parameters were found to be statistically different between control and BDV positive groups (p<0.01), total protein, alkaline phosphotase, creatine kinase, amylase, glucose, and high-density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Ballesteros et al (2010) reported that an increase in the Hematocrit and RBC value and Hgb concentration significantly different but they were not detected by any statistically significant differences in MCV, MCH, MCHC values between MVV positive and negative animals. RBC, MCH and Hgb has notspecific parameters for MVV or any diseases; therefore changes of these parameters could be associated with other conditions (Gazyagci et al, 2010). Lipecka et al (2010) reported that monocytes, macrophages lineage and mononuclear cells are the target for MVV (Lipecka et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Ballesteros et al (2010) reported that an increase in the Hematocrit and RBC value and Hgb concentration significantly different but they were not detected by any statistically significant differences in MCV, MCH, MCHC values between MVV positive and negative animals. RBC, MCH and Hgb has notspecific parameters for MVV or any diseases; therefore changes of these parameters could be associated with other conditions (Gazyagci et al, 2010). Lipecka et al (2010) reported that monocytes, macrophages lineage and mononuclear cells are the target for MVV (Lipecka et al, 2010).…”
Section: Discussionmentioning
confidence: 99%